Local Delivery of Therapeutic Boron for Bone Healing Enhancement. Issue 5 (May 2021) - Hadidi, Lina; Ge, Susan; Comeau-Gauthier, Marianne; Ramirez-Garcia Luna, Jose; Harvey, Edward J.; Merle, Geraldine
Abstract : Objectives: To evaluate if local delivery of boron can accelerate bone healing and examine if the bioactive salt impacts the osteogenic response of bone-derived osteoclasts and osteoblasts by the regulation of the Wnt/β-catenin pathway. Methods: Bilateral femoral cortical defects were created in 32 skeletally mature C57 mice. On the experimental side, boric acid (8 mg/kg concentration) was injected locally, whereas on the control side, saline was used. Mice were euthanized at 7, 14, and 28 days. MicroCT was used to quantify bone regeneration at the defect. Histological staining for alkaline phosphatase and tartrate-resistant acid phosphatase was used to quantify osteoblast and osteoclast activity, respectively. Immunohistochemical antibodies, β-catenin, and CD34 were used to quantify active β-catenin levels and angiogenesis, respectively. Results: The boron group exhibited higher bone volume and trabecular thickness at 28 days on microCT. Both alkaline phosphatase activity and β-catenin activity was significantly higher in the boron group at 7 days. In addition, CD34 staining revealed increased angiogenesis at 14 days in boron-treated groups. We found boron to have no association with osteoclast activity. Conclusions: This study shows that local delivery of boron is associated with an increase in osteoblast activity at early phases of healing. The corresponding increase in β-catenin likely supports that boron increases osteoblast activity by the Wnt/β-catenin pathway. Increased angiogenesis at 14 days could be a separate mechanism of increasing bone formation that is independent of Wnt/β-catenin activation. Abstract : Supplemental Digital Content is Available in the Text.